Lacan and the Nonhuman (The Palgrave Lacan Series, 2018)
This book initiates the discussion between psychoanalysis and recent humanist and social scientific interest in a fundamental contemporary topic - the nonhuman. The authors question where we situate the subject (as distinct from the human) in current critical investigations of a nonanthropoentric universe. In doing so they unravel a less-than-human theory of the subject; explore implications of Lacanian teachings in relation to the environment, freedom, and biopolitics; and investigate the subjective enjoyments of and anxieties over nonhumans in literature, film, and digital media. This innovative volume fills a valuable gap in the literature, extending investigations into an important and topical strand of the social sciences for both analytic and pedagogical purposes.